Towards a definition of efforts - Massin, Olivier (My University, 2017)
Although widely used across psychology, economics, and philosophy, the concept of effort is rarely ever defined. This article argues that the time is ripe to look for an explicit general definition of effort, makes some proposals about how to arrive at this definition, and suggests that a force-based approach is the most promising. Section 1 presents an interdisciplinary overview of some chief research axes on effort, and argues that few, if any, general definitions have been proposed so far. Section 2 argues that such a definition is now needed and proposes a basic methodology to arrive at it, whose first step is to make explicit the various tacit assumptions about effort made across sciences and ordinary thinking. Section 3 unearths 4 different conceptions of effort from research on effort so far: primitive-feelings accounts, comparator-based accounts, resource-based accounts and force-based accounts. It is then argued that the first 2 kinds of accounts, although interesting in their own right, are not strictly speaking about effort. Section 4 considers the 2 most promising general approaches to efforts: resource-based and force-based accounts. It argues that these accounts are not only compatible but actually extensionally equivalent. This notwithstanding, it explains why force-based accounts should be regarded are more fundamental than resource-based accounts.